KISI-KISI SOAL DALAM EVALUASI PENDIDIKAN - Warih Nurul Hidayati; Solekhah Nur Afifah; Achmad Rasyid Ridha (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
The question grid is a very crucial supporting instrument in the educational evaluation process. The grid functions as a systematic guideline to ensure that the questions compiled reflect the competencies to be achieved, the material that has been taught, and the appropriate cognitive level. With the grid, the compilation of questions becomes more focused, objective, and consistent with learning objectives. Evaluation research and practice show that the use of good grids can increase the validity and reliability of learning outcome measurement tools. Therefore, an understanding of the principles, components, and techniques for compiling grids is very important for educators and evaluation developers.